Values that work: Exploring the moderator role of protestant work ethics in the relationship between human resources practices and work engagement and organizational citizenship behavior - Carolina Zú\~niga; David Aguado; Patricio Cabrera-Tenecela (Administrative Sciences, 2022)
This research aimed to analyze the moderating effect that Protestant work ethics (PWE) have on the relationship between human resources practices (HRP) and (a) work engagement (WE) and (b) organizational citizenship behavior (OCB). The sample consisted of 299 participants. The results revealed that PWE moderates the relationship between HRP and WE and OCB through five dimensions. The dimensions of PWE-leisure and PWE-centrality of work are moderators between the HRP and the WE. The dimensions of PWE-morality-ethics, PWE-wasted time, PWE-delay of gratification, and PWE-leisure moderate the relationship between HRP and OCB. The analysis offers additional evidence to existing literature in understanding how human resources practices facilitate the development of work engagement and citizenship behaviors. The workers' values play an essential role here to strengthen that relationship and mitigate its harmful effects.
Keywords: 350; human resources practice; moderation analysis; organizational citizenship behavior; Protestant work ethic; work engagement